2019
DOI: 10.1002/mgg3.666
|View full text |Cite
|
Sign up to set email alerts
|

Further support linking the 22q11.2 microduplication to an increased risk of bladder exstrophy and highlighting LZTR1 as a candidate gene

Abstract: Background The bladder exstrophy‐epispadias complex (BEEC) is a congenital malformation of the bladder and urethra. The underlying causes of this malformation are still largely unknown; however, aside from environment, genetics is thought to play an essential role. The recurrent 22q11.2 microduplication is the most persistently detected genetic aberration found in BEEC cases. Methods We performed array comparative genomic hybridization (array‐CGH) analysis of 76 Swedish BEEC patients. Statistical analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…We have previously identified altogether five typical 22q11‐duplications associated with BEEC (Lundin et al, 2010 , 2019 ). The prevalence in our material is 3.4% in reported BEEC patients as compared with 0.08% in controls (Lundin et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously identified altogether five typical 22q11‐duplications associated with BEEC (Lundin et al, 2010 , 2019 ). The prevalence in our material is 3.4% in reported BEEC patients as compared with 0.08% in controls (Lundin et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…All BEEC patients, adults and children, were recruited from the Pediatric Surgery Departments in Stockholm, Göteborg, Uppsala, and Lund, Sweden. Six patients with previously published chromosome aberrations were excluded from the study (Lundin et al, 2010 , 2019 ; Soderhall et al, 2014 ). Blood or excess bladder or skin tissue obtained during surgery was collected for DNA isolation and molecular genetic analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with data from other studies that identified 22q11 duplications in approximately 3% of cases (Table 3). This is the most strongly associated genetic variation with BEEC, conferring a twelve-to-thirty-fold increased risk [55,56]. It is possible that the origin of the allele (paternal or maternal) that the duplication has arisen on, or the parent from whom the duplication has been inherited, alters the risk of BEEC.…”
Section: Chromosome 22q11 Micro Duplications and Beecmentioning
confidence: 99%